Draft of a biography of Samuel P. Massie (1987)
Draft of a biography of Samuel P. Massie (1919-2005). Massie was an African American chemist who researched the synthesis and development of therapeutic drugs, focusing on treating malaria, herpes, meningitis, and gonorrhea.
Keywords: Massie, Samuel; African American scientists; Scientists; Chemists; African American chemists; Biographies